A PELATIHAN PEDAGOGIK DIGITAL BERSAMA GURU SMP UNISMUH MAKASSAR DALAM MENDISAIN MODEL PEMBELAJARAN MODEL INTERAKTIF BERBASIS GOOGLE FOR EDUCATION : PELATIHAN PEDAGOGIK DIGITAL BERSAMA GURU SMP UNISMUH MAKASSAR DALAM MENDISAIN MODEL PEMBELAJARAN MODEL INTERAKTIF BERBASIS GOOGLE FOR EDUCATION - Maria Ulviani Ulfa; Sujariati (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
The aim of this dedication are to improve the teachers’ pedagogy competence, to improve the teachers’ ability in applying teaching model in online learning. The activity in this study proposed participatory method. it means that the proposer and mitra are proactive in doing process activity. Moreover, the social approach also used by proposer for solve the primary problem in teaching learning online process that is in service of training and associating program. In getting data from this activity, the proposer distributed questionnaire to the participant to find out the three aspects as variable namely aspect of compatibility, usability, and satisfaction. One of media interaction that used in this dedication activity is google classroom. the output of this activity is expected form the teacher in adapting situation on some model of online learning process, implemented pedagogy digital on the teaching learning online process especially in using google classroom so it can also be facility for students collecting task assignment, for evaluating the students’ task. However, the teachers can provide persuasive approach to developing students’ learning. Furthermore, from this activity, the teachers’ able design learning module dealt with interactive and innovative model learning.